Two in one: a randomized controlled trial on an internet-based intervention (Lenio) for management of both chronic pain and depressive symptoms - Borsutzky, Swantje; Wilke, Anna-Sophie; Gehlenborg, Josefine; Moritz, Steffen (Frontiers in Psychiatry, 2025)
The high prevalence of chronic pain and comorbid depression, along with their negative impacts on individuals and society, highlights the need for accessible and effective interventions. This study examined the feasibility, efficacy, and acceptability of Lenio, an Internet-based self-help intervention, combined with the COGITO smartphone application for managing these conditions. The randomized controlled trial involved an intervention group (IG) using Lenio and COGITO, an active control group (ACG) using a transdiagnostic app, and a wait-list control group (WCG) receiving usual treatment. Lenio incorporates cognitive behavioral therapy and third-wave techniques, supported by COGITO’s gamified daily exercises to enhance adherence. Across 263 participants assessed at three intervals over 16 weeks, the IG showed significant improvement in somatic-affective depressive symptoms compared to the WCG post-intervention and both control groups at follow-up. However, the ACG outperformed the IG in managing pain at post-intervention though these effects did not persist until follow-up. The interventions were well-received and feasible, with older participants benefiting more from the Lenio/COGITO combination. Lenio and COGITO could bridge gaps to conventional therapy, potentially easing pain by enhancing psychological well-being and coping strategies. Future studies should investigate tailored interventions for chronic pain and their long-term effectiveness.ProtocolFull trial protocol can be accessed via DOI: 10.1186/s13063-023-07440-8.Clinical trial registrationhttps://drks.de/register/de/trial/DRKS00026722/preview, identifier DRKS-IDDRKS00026722.